2006
DOI: 10.1007/s00125-006-0282-8
|View full text |Cite
|
Sign up to set email alerts
|

Paternal insulin resistance and its association with umbilical cord insulin concentrations

Abstract: Aims/hypothesis: Fetal growth is influenced by genetic factors as well as the intra-uterine environment. We hypothesised that some genetic factors may alter fetal insulin secretion and insulin action. Subjects, materials and methods: To assess this, we analysed plasma insulin concentration in umbilical cord blood from 644 normal, term, UK Caucasian deliveries from the Exeter Family Study of Childhood Health. We tested for associations between cord insulin and each of parental anthropometry, fasting glucose, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
(44 reference statements)
4
13
0
Order By: Relevance
“…Our findings, that gestational age, parity, maternal birth weight and BMI independently influence birth weight for both boys and girls is in accordance with previous reports (Catalano et al 1998, Shields et al 2006. however, after adjusting for these variables, paternal birth weight had a significant effect on birth weight of boys but not for girls.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings, that gestational age, parity, maternal birth weight and BMI independently influence birth weight for both boys and girls is in accordance with previous reports (Catalano et al 1998, Shields et al 2006. however, after adjusting for these variables, paternal birth weight had a significant effect on birth weight of boys but not for girls.…”
Section: Discussionsupporting
confidence: 93%
“…Under these circumstances, paternally inherited insulin resistance may be compensated by increases in fetal insulin production. This suggestion was supported by their observation that paternal insulin resistance was inversely correlated with fetal insulin concentrations (17). In a subset of our study population, we were unable to detect such a relationship between paternal insulin resistance and fetal cord blood insulin or C-peptide levels.…”
Section: Discussionmentioning
confidence: 76%
“…This is a situation similar to the difference seen between Indian and U.K. babies (10), where Indian babies are smaller with more adipose tissue and higher insulin concentrations, which is thought to reflect insulin resistance because the increase in cord insulin is not associated with augmented growth. Research has also shown that babies born to the most insulin-resistant fathers have higher cord insulin concentrations compared with babies born to the least insulin-resistant fathers when matched for birth weight, further supporting the idea that increased cord insulin without increased growth represents an insulin-resistant phenotype (20).…”
Section: Relationships With Mode Of Deliverymentioning
confidence: 83%